Educational immigrants: evidence from Chinese young entrepreneurs in the UK. Issue 1 (31st May 2019) - Chen, Wei; Tajeddini, Kayhan; Ratten, Vanessa; Tabari, Saloomeh
Abstract : Purpose: While the contribution of educational students to the economies of developed countries is critical, educational immigrants rarely find employment in the regulated unionized sectors of these countries and are found instead setting up their own business. The purpose of this paper is to understand how educational immigrants use their cultural and social heritage for entrepreneurial purposes. Design/methodology/approach: A qualitative method was undertaken, comprising face-to-face in-depth interviews with 12 respondents, involved in the hospitality industry for various purposes such as inspiration, challenges, frustrations and attracting investments. A convenience sampling method coupled with snowball sampling was chosen because of the availability of the informants and their willingness to be a part of the study. A thematic analysis was conducted in the transcripts of interviews to understand the aim and motivation factors of each individual followed by content analysis process. Findings: The findings reveal that, while the informants suffer of language barriers, lack or shortage of experience in understanding the laws and legislations, unfamiliarity with the host culture, as well as financial constraints, the entrepreneurial sprite drives them to establish their businesses. Research limitations/implications: This study has important consequences for understanding how educational immigrants transition from an educational to a business setting. Practical implications: As the increase in educational immigrants becomes more important to the economic and social performance of countries, it is important to understand how young entrepreneurs start their businesses. Originality/value: Educational immigrants are an important source of regional innovation and development. This paper focuses on the role of international higher education and the link to entrepreneurship by focusing on young Chinese entrepreneurs.